Development of a rapid phenotypic test for HCV protease inhibitors with potential use in clinical decisions - Luciana Santos Pessoa; Luãnna Liebscher Vidal; Emmerson C.B. da Costa; Celina Monteiro Abreu; Rodrigo Delvecchio da Cunha; Ana Luiza Chaves Valadão; André Felipe dos Santos; Amilcar Tanuri (Genetics and Molecular Biology)
Abstract Approximately 185 million people worldwide are chronically infected with hepatitis C virus (HCV). The first-wave of approved NS3 protease inhibitors (PIs) were Telaprevir and Boceprevir, which are currently discontinued. Simeprevir is a second-wave PI incorporated into the Brazilian hepatitis C treatment protocol. Drug resistance plays a key role in patients' treatment regimen. Here, we developed a simple phenotypic assay to evaluate the impact of resistance mutations in HCV NS3 protease to PIs, using a protein expression vector containing wild type NS3 protease domain and NS4A co-factor. We analyzed the impact of five resistance mutations (T54A, V36M, V158I, V170I and T54S+V170I) against Telaprevir, Boceprevir and Simeprevir. Protein purifications were performed with low cost methodology, and enzymatic inhibition assays were measured by FRET. We obtained recombinant proteases with detectable activity, and IC50 and fold change values for the evaluated PIs were determined. The variant T54A showed the highest reduction of susceptibility for the PIs, while the other four variants exhibited lower levels of reduced susceptibility. Interestingly, V170I showed 3.2-fold change for Simeprevir, a new evidence about this variant. These results emphasize the importance of enzymatic assays in phenotypic tests to determine which therapeutic regimen should be implemented.